Impact of Carbon Disclosure, Profitability, and Manajerial Ownership on Firm Value with Dividend Moderation - Chika Windia A; Nailah Apriyuni; Acep Komara (Akuisisi : Jurnal Akuntansi, 2025)
This study analyzes the influence of carbon emission disclosure, profitability, and managerial ownership on firm value, with dividend policy as a moderating variable. The research focuses on non-cyclical food and beverage companies listed on the Indonesia Stock Exchange (IDX), using a quantitative method and Moderated Regression Analysis (MRA). The results show that all three variables have a significant positive effect on firm value; however, their influence weakens when moderated by dividend policy. The findings highlight the importance of environmental transparency, operational efficiency, and ownership structure in maintaining investor confidence and enhancing firm value. The study suggests that companies should be more transparent in disclosing carbon emissions, improve profitability sustainably, and manage dividend policies wisely.